STUDY OF GENOME SEQUENCES USING GRAPH THEORY - V. Krishnan; A. Reigana Begum (Utilitas Mathematica, 2025)
This paper proposes a novel study of genome sequences using graph theoretic tools. A genome sequence is a characteristic sequence of four ‘Nucleotides’ such as ‘Adenine’, ‘Thymine’, Guanine, ‘Cytosine’. These four macromolecules are represented by their first letters such as A, T, G and C respectively. Genome is entire set of DNA instructions found in a cell. Human genome consists of 23 pairs of chromosomes located in the cell’s nucleus, as well as a small chromosome in the cell’s mitochondria. Genome contains all relevant information needed for an individual to grow and function. Human genome contains about 3 billion nucleotides. A sequence of three consecutive nucleotides is called ‘Codon’, to be more specific, a ‘Triplet Codon’. One can construct 64 triplet codons from four nucleotides. During protein synthesis inside a cell, the protein called ‘Ribosome’ makes use of sequence of triplet codons, chooses amino acids and builds required proteins. These triplet codons play a vital role in the cell action. In a codon sequence, adjacent codons overlap by one nucleotide or by two nucleotides. All hereditary properties of an individual are decided by these overlaps. This paper introduces the structure of overlapping and non-overlapping codons using graph theoretic tools.